Pengaruh Latihan Range of Motion terhadap Intensitas Nyeri pada Pasien Post Operasi Fraktur di RSUD Dr. Pirngadi Medan - Budiana Yazid; Rina Rahmadani Sidabutar (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
Range of motion exercises in postoperative fracture patients can improve blood circulation, reduce pain and accelerate wound healing. If the pain that is felt is not handled properly, the patient will feel afraid when he will move, and cause blood circulation to the part that is being operated on is not smooth. The purpose of this study was to determine the effect of range of motion exercises on pain intensity in postoperative fracture patients. This research method uses a one group pretest post test design, this study does not have a control group but in this research design initial observations (pre-test) have been carried out. The sampling technique used in this research is total sampling. Bivariate test using paired t-test. Where the p-value is 0.000 <0.05, which means that there is an effect of range of motion exercises on pain intensity in postoperative fracture patients.